An annotated checklist of Acanthocephala from Australian fish - Smales, Lesley R; Weaver, Haylee J (Zootaxa, 2015)
Thirty one genera, comprising 58 named species, 15 undetermined species and nine species known only as cystacanths from paratenic fish hosts were found infesting 144 marine, esturine and freshwater species of fish from Australian and Australian Antarctic waters. Host habitats are given and the distribution and records of the acanthocephalans are given. A key to these parasites at the generic level is provided.